Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT. Bineatama Kayone Lestari Tasikmalaya - Fauzan (PT Maju Malaqbi Makkarana, 2023)
This research was conducted with the aim of knowing the effect of organizational culture and work environment on employee performance in the Barecore Division of PT. Bineatama Kayone Lestari Tasikmalaya. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 100 respondents who are employees of the Barecore Division of PT. Bineatama Kayone Lestari Tasikmalaya. The technique used in this research is multiple linear regression analysis. Based on the research results, it can be seen that organizational culture has a significant effect on employee performance, work environment has a significant effect on employee performance, organizational culture and work environment has a significant effect on employee performance in the barecore division of PT. Binetama Kayone Lestari Tasikmalaya.